2018
DOI: 10.1007/s12070-018-1482-5
|View full text |Cite
|
Sign up to set email alerts
|

Aural Polyp is not Always Due to Chronic Otitis Media (COM): Preoperative Computed Tomographic Scan is Good Pointer for Sinister Lesions

Abstract: Twenty five patients of aural polyp who underwent canal wall down mastoidectomy were analysed retrospectively. Histopathological examination revealed cholesteatoma in 22 (88%) patients. However, histopathological diagnosis in 3 of these patients was unusual and rare benign tumors of the middle ear cleft-meningioma, neurilemmoma and capillary hemangioma. Review of the preoperative High Resolution Computed Tomography (HRCT) temporal bone revealed an unusual picture in all of the three cases. Features noted were:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The prevalence of cholesteatoma obtained in this study was 58%, which is in accordance with Milroy et al (9), López Aguado et al (10), and Arroyo Gargallo et al (11) who observed prevalence of cholesteatoma in patients with polyps of 43.7%, 50%, and 52%, respectively. Other authors, such as Xenellis et al (7) and Kalra et al(2) obtained a higher prevalence of cholesteatomas: 86.7% and 88%, respectively. All these studies were retrospective and subject to several biases inherent to the nature of this study design.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The prevalence of cholesteatoma obtained in this study was 58%, which is in accordance with Milroy et al (9), López Aguado et al (10), and Arroyo Gargallo et al (11) who observed prevalence of cholesteatoma in patients with polyps of 43.7%, 50%, and 52%, respectively. Other authors, such as Xenellis et al (7) and Kalra et al(2) obtained a higher prevalence of cholesteatomas: 86.7% and 88%, respectively. All these studies were retrospective and subject to several biases inherent to the nature of this study design.…”
Section: Discussionmentioning
confidence: 82%
“…It was also possible to determine that polyps were not associated with greater involvement of the facial nerve, since it was only involved in 6 (7.4%) cases in this sample, and in 4 of them, the underlying disease was a neoplasm. This sign was also associated with malignancy according to Xenellis et al (7) and also had a low prevalence according to Kalra et al (2).…”
Section: Discussionmentioning
confidence: 87%
“…Tegmen erosion can happen secondary to any extensive squamous disease, due to underlying inflammatory or malignant pathology, trauma, and/or brain herniation 7,9,10 . In our study, the brain herniation presented as an aural polyp.…”
Section: Discussionmentioning
confidence: 99%